2016
DOI: 10.1111/cdev.12676
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Support of Children's Early Numerical Concept Learning Predicts Preschool and First‐Grade Math Achievement

Abstract: The primary goal in this study was to examine maternal support of numerical concepts at 36 months as predictors of math achievement at 4½ and 6-7 years. Observational measures of mother-child interactions (n = 140) were used to examine type of support for numerical concepts. Maternal support that involved labeling the quantities of sets of objects was predictive of later child math achievement. This association was significant for preschool (d = .45) and first-grade math (d = .49), controlling for other forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…Future research can further investigate whether certain numeracy activities are more effective in predicting children's later learning outcomes than some other numeracy activities (e.g. one-to-one counting and labeling set sizes; Casey et al, 2018). Secondly, SES is indicated in this study by parental educational and professional levels.…”
Section: Limitations Of This Study and Suggestions For Future Researchmentioning
confidence: 95%
“…Future research can further investigate whether certain numeracy activities are more effective in predicting children's later learning outcomes than some other numeracy activities (e.g. one-to-one counting and labeling set sizes; Casey et al, 2018). Secondly, SES is indicated in this study by parental educational and professional levels.…”
Section: Limitations Of This Study and Suggestions For Future Researchmentioning
confidence: 95%
“…Some inconsistencies have been found in previously conducted studies. Some studies have found a positive effect of early numeracy activities at home on later mathematics achievement (Casey et al, 2018;Chiu, 2018;Galindo & Sonnenschein, 2015;Huang et al, 2017;LeFevre et al, 2009;Niklas & Schneider, 2017;Zhu & Chiu, 2019), while others have found a mixed or nonsignificant effect (Blevins-Knabe et al, 2000;Missall et al, 2015;Skwarchuk, 2009;Skwarchuk et al, 2014;Zhang et al, 2020). These inconsistent findings might be because previously conducted studies have not properly considered the effect of a student's background and examined small non-representative samples (Zhu & Chiu, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Other recent work found that children exposed to more conversations about math broadly (i.e., math talk) tend to score higher on a standardized test of mathematical ability one year later (Susperreguy & Davis‐Kean, ). In addition, parental labeling of quantities (i.e., talking about cardinality) when children are 3 years old is a better predictor of math achievement in preschool and first grade than parental identification of numerals or counting (Casey et al, ). Finally, previous work has separated parental elicitations of math talk (e.g., “How many pennies are there?”) and statements about math (e.g., “You have three pennies.”), but neither seem to separately predict children's later math abilities (Casey et al, ).…”
mentioning
confidence: 99%
“…In addition, parental labeling of quantities (i.e., talking about cardinality) when children are 3 years old is a better predictor of math achievement in preschool and first grade than parental identification of numerals or counting (Casey et al, ). Finally, previous work has separated parental elicitations of math talk (e.g., “How many pennies are there?”) and statements about math (e.g., “You have three pennies.”), but neither seem to separately predict children's later math abilities (Casey et al, ). Thus, these studies highlight the importance of parental math talk for young children's math abilities, though the overall frequency of parental math talk in everyday contexts is fairly low and there might be differences between different aspects of math talk.…”
mentioning
confidence: 99%
See 1 more Smart Citation